(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article discusses the effectiveness and usefulness of circuit training for improving the overall physical fitness of qualified boxers . Circuit training is a type of training aimed at maximally loading the body and developing each muscle group by performing various exercises in sequence. Taking the above into account, the article has developed a set of circuit exercises and outlined the necessary instructions.